1991
DOI: 10.2527/1991.69124696x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an implant of trenbolone acetate and estradiol on growth, feed efficiency, and carcass composition of Holstein and beef steers1

Abstract: The effects of an implant of 140 mg of trenbolone acetate and 28 mg of estradiol (TBA + E2) on performance and carcass composition were evaluated with 72 individually fed steers. Holstein (n = 24), Angus (n = 24), and Angus x Simmental (n = 24) steer calves were allocated by breed and implant treatment to either an individual feeding pen (n = 36) or an electronic feeding door in a group pen (three pens with 12 animals per pen). Intake and refusal of the 85% concentrate diet were recorded daily. Animals were sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
54
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 6 publications
9
54
0
1
Order By: Relevance
“…Previous work has shown that implants increase HCW compared with nonimplanted cattle; however, when different implant treatments are compared, little difference exists between HCW (Samber et al, 1996;Scaglia et al, 2004;Bruns et al, 2005), as was the case in the current study. Several studies have shown little effect of implant on external FT (Perry et al, 1991;Pritchard, 1994;Samber et al, 1996;Scaglia et al, 2004;Bruns et al, 2005), LM area (Samber et al, 1996;Scaglia et al, 2004;Bruns et al, 2005), and KPH fat (Foutz et al, 1990;Samber et al, 1996;Bruns et al, 2005), which is in agreement with the present study. The major focus of this study was to determine the impact of delaying the initial feedlot implant on QG in calf-fed steers.…”
Section: Carcass Characteristicssupporting
confidence: 83%
“…Previous work has shown that implants increase HCW compared with nonimplanted cattle; however, when different implant treatments are compared, little difference exists between HCW (Samber et al, 1996;Scaglia et al, 2004;Bruns et al, 2005), as was the case in the current study. Several studies have shown little effect of implant on external FT (Perry et al, 1991;Pritchard, 1994;Samber et al, 1996;Scaglia et al, 2004;Bruns et al, 2005), LM area (Samber et al, 1996;Scaglia et al, 2004;Bruns et al, 2005), and KPH fat (Foutz et al, 1990;Samber et al, 1996;Bruns et al, 2005), which is in agreement with the present study. The major focus of this study was to determine the impact of delaying the initial feedlot implant on QG in calf-fed steers.…”
Section: Carcass Characteristicssupporting
confidence: 83%
“…Treatment effects on growth performance of Holstein bull calves are presented in the Table. Compared with nonimplanted controls, implanting increased (P < 0.01) the overall day 56 DMI (8.3%), ADG (18.5%), gain efficiency (ADG:DMI, 7.9%), dietary NE m and NE g (5.6% and 6.4%, respectively), and apparent energy retention per unit of DMI (7%). These results are consistent with previous studies involving calffed Holstein steers, wherein implanting improved ADG by 12% to 18% and gain efficiency by 7% to 12% (13,14). Zinn , and SBW is the average SBW.…”
supporting
confidence: 83%
“…In their review of the literature, Duckett and Pratt (2014) stated that anabolic implants do not or minimally influence 12th rib BF thickness. Perry et al (1991), Gerken et al (1995), and Roeber et al (2000) reported that various anabolic implants do not influence BF thickness. In the current study, BF thickness tended to be reduced by 25% in the IMP carcasses.…”
Section: Growth-promoting Technologies Effectsmentioning
confidence: 99%